AN OVERVIEW OF PROTECTIVE LAW ENFORCEMENT CONSUMERS (BPSK DECISION STUDY No.01/BPSK/MDN/2003) - Joharsyah, Joharsyah; Wooton, Ian; Setiawan, Ben; K Tarigan, Adrian; Florenta Butar-Butar, Diana (Universitas Efarina, 2021)
Initially, this research on consumer protection in Indonesia by the government did not have a specific law, but the legal instruments were scattered in several laws that only limited certain consumers, for example electricity, health, small businesses, food and others. After the reform under the leadership of President BJ. Habibie only then had a special law governing consumer protection, which actually originated from the DPR's initiative, namely Law no. 8 of 1999 which was ratified on April 20, 1999 State Gazette of 1999 No. 42. The decision issued by the Consumer Dispute Settlement Agency (BPSK) Medan City 01/BPSK/MDN/2003 against brother P. Silalahi's lawsuit against Macan Yaohan Merak Jingga complies with the provisions stipulated in Law no. 8 of 1999 concerning Consumer Protection, the provision referred to is Business Actors. Obliged to provide clear, correct and honest information regarding the conditions and warranties of goods and or services as well as provide explanations and use of repair and maintenance. Another provision is that Business Actors are required not to resell expired biscuits by replacing/re-melting or changing the expiration date, month and year. The BPSK Panel of Judges could not grant other matters, namely an apology to Mass Media because it was not regulated in Law no. 8 of 1999. Another provision is that Business Actors are required not to resell expired biscuits by replacing/re-melting or changing the expiration date, month and year. The BPSK Panel of Judges could not grant other matters, namely an apology to Mass Media because it was not regulated in Law no. 8 of 1999. Another provision is that Business Actors are required not to resell expired biscuits by replacing/re-melting or changing the expiration date, month and year. The BPSK Panel of Judges could not grant other matters, namely an apology to Mass Media because it was not regulated in Law no. 8 of 1999.